Preparasi dan Karakteristik Fisis Nanopartikel Magnetit (Fe3O4) - Agus Riyanto (Jurnal Fisika FLUX, 2019)
This study aims to identify the effect of preparation temperature on microstructure and magnetic properties of magnetite nanoparticles prepared from FeSO4.7H2O and FeCl3.6H2O by using co-presipitation method without organic solvent and surfactant. Precursors were prepared at 30 oC, 60 oC, and 90 oC under atmospheric pressure. Microstructure and diameter distribution of magnetite nanoparticles were analyzed by using XRD, FTIR, TEM, and imageJ software, while the magnetic properties were analized using VSM. The identification result show that the magnetite phase was formed on all samples with polycrystalline structure. The increasing of preparation temperature was followed by increase in diameter of grains and oxidation rate of magnetite phase into maghemit ( -Fe2O3). The superparamagnetic properties almost can be observed especially in sample prepared at 30 oC, where magnitude of remanent and coersivity is 3.39 emu/g and 23.93 Oe, respectively. The magnitude of remanent and coersivity increases as preparation temperature increases and superparamagnetic effect decrease.KEYWORD :